Regional age structure and economic growth: an econometric study for German regions - Stephan Brunow; Georg Hirte (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2009)
This paper analyses the impact of the regional age structure on growth of German regions. Based on a neoclassical growth model an augmented Solow model was derived and estimated in a spatial econometric approach. Besides labor and human capital, public spendings and urbanisation measures are controlled for. Adding the age structure of the employed labor force, which we use as proxy for the age pattern of human capital, improves the regression model significantly. Spatial autocorrelation is controlled for and supports OLS results. To get deeper insights in the effectiveness of the age structure quantile regression techniques are applied to distinguish the effects between various levels of growth rates. The results of the different estimation approaches provide evidence that the age structure matters for growth.
Keywords: J1; R11; R53; 330; age structure; growth; public spending